2022
DOI: 10.56093/ijas.v91i12.120804
|View full text |Cite
|
Sign up to set email alerts
|

Self-reliant in year-round vegetable production through kitchen garden in Indo-Gangetic Plains

Abstract: The government of India has long been striving to increase the food and nutritional security of rural and urban households. In this regard, kitchen/homestead gardens of limited available space can play an important role in fullfilling the demand for year-round diversified vegetable requirements. Considering the scope to self-reliant in year-round vegetable production and consumption through kitchen garden model, a field experiment was conducted for consecutive two years (2018–19) at the homestead garden of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to (Meena and Singh, 2014), this trend is predicted to persist, (Singh et al 2017), there has been a significant increase in vegetable productivity through both open field and protected cultivation methods. However, it is important to highlight that this progress has been by an escalation in the use of fertilizers and pesticides, as noted by (Noopur et al 2021). (Noopur et al 2023) emphasized the importance of vegetables as they are rich sources of essential vitamins, minerals, and fiber.…”
Section: Introductionmentioning
confidence: 99%
“…According to (Meena and Singh, 2014), this trend is predicted to persist, (Singh et al 2017), there has been a significant increase in vegetable productivity through both open field and protected cultivation methods. However, it is important to highlight that this progress has been by an escalation in the use of fertilizers and pesticides, as noted by (Noopur et al 2021). (Noopur et al 2023) emphasized the importance of vegetables as they are rich sources of essential vitamins, minerals, and fiber.…”
Section: Introductionmentioning
confidence: 99%
“…So, there is an urgent need to develop a new natural, effective, and safe preservative as an alternative to these harmful ones [1,6]. In this perspective, work has been carried out on the bacteriocins of lactic bacteria isolated from milk and fruits to understand their structure-function relationships and their mode of action and to promote their applications in the fight against pathogens, in particular multidrug resistant (MDR) [5,[7][8][9][10]. Indeed, some studies have reported that bacteriocins such as nisin, mersacidin, or lacticin can be considered as an alternative to control the proliferation of pathogenic bacteria in foods [11] and even those that are resistant to antibiotics [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have highlighted the harmful effect of these preservatives on the health of consumers [ 2 ]. These chemicals can lead to several diseases such as colon cancer, which are more observed in recent decades and related to the side effects caused by the abuse or overuse of chemical preservatives (E249 to E252) according to some studies [ 3 – 5 ]. So, there is an urgent need to develop a new natural, effective, and safe preservative as an alternative to these harmful ones [ 1 , 6 ].…”
Section: Introductionmentioning
confidence: 99%